The Use of Communicative Language Teaching (CLT) Approach in Teaching Speaking Skill : A Descriptive Qualitative Study at The 7th Grade of Binar Ilmu Boarding School - Alia Nurdayani; Rahma Sakina; Aip Syaepul Uyun (Universitas Subang, 2024)
Speaking is one of four English skills that students must master because it is an important skill. To teach speaking, teachers can use Communicative Language Teaching (CLT) approach. The main purposes of this research are to find out the students' response to the CLT in teaching speaking, to figure out the problems faced by teacher in using CLT in teaching speaking, and to explore how teacher solves problems encountered in using CLT in teaching speaking. This study was conducted at a private junior high school in North Bandung. A descriptive qualitative research design was employed in this study with three data collection techniques, namely observation, questionnaire and interview. The participants involved were an English teacher and 27 students of the 7th grade of Binar Ilmu Junior High School. To analyze the data, a framework of CLT proposed by Richards & Rodgers, (2014) was used. The results show that the students responded positively to the use of CLT in teaching speaking skill. Furthermore, there were three problems faced by the teacher in the use of CLT, namely the lack of students’ interaction, the limited students’ concentration, and the limited time allocation. To overcome those problems, the teacher did such things as provoking students by asking questions or inviting discussions, giving some signals such as yells to make the students conducive, delivering one material in two meetings, and giving them homework